Efektivitas Terapi Kombinasi Metformin dengan Habbatussauda (nigella sativa) dalam Penurunan Kadar Glukosa Darah pada pasien Diabetes Mellitus: Effectiveness of Combination Therapy of Metformin and Black Seed (Nigella sativa) in Reducing Blood Glucose Levels in Patients with Diabetes Mellitus - Widiasari, Santi; Siregar, Teddy Syah (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
The prevalence of diabetes mellitus is estimated to increase to 111.2 million people aged 65-79 years. This figure will further increase to 578 million in 2030 and 700 million in 2045. Based on region, Southeast Asia is ranked 3rd with a prevalence of diabetes mellitus of 11.3%. Metformin is indicated for treatment in patients with increased blood glucose, but has side effects in the form of lactic acidosis in patients with hypoxemia, alcoholism, cirrhosis, sepsis, shock, and contrast exposure as well as gastrointestinal side effects. The aim to analyze the effect of using combination therapy of metformin with black seed (Nigella sativa) in reducing blood glucose levels in diabetes mellitus patients. Method: This research uses analytical observational research with a cross sectional method. The sampling technique was purposive sampling in diabetes mellitus patients who were using metformin therapy at SIAK Regional Hospital with a sample of 7 patients who were using metformin and 7 patients who were using combination thrapy of metformin with Black Seed. The data will be analyzed using the Independent T test because it meets the parametric requirements with a p-value > 0.05. In this study it was found that the difference in the decrease in blood glucose levels during the metformin therapy group was greater than in the combination therapy group with the normality test results showing a p-value >0.05 which means the data is normally distributed. In the results of the independent t-test, the p value was obtained (0.332), which means there was no effect on reducing blood glucose levels in the metformin therapy group with black seed. Based on the presentation of the research results, it can be concluded that the combination therapy of black seed and metformin does not significantly reduce blood glucose levels in diabetes mellitus patients with a p value >0.332, meaning that there is no significant effect on the use of the combination therapy of black seed and metformin.